2019
DOI: 10.1039/c9na00658c
|View full text |Cite
|
Sign up to set email alerts
|

Nano-SiO2 coating enabled uniform Na stripping/plating for dendrite-free and long-life sodium metal batteries

Abstract: Metallic sodium, which has a suitable redox potential and high theoretical capacity, is regarded as an ideal anode material for rechargeable Na metal batteries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 51 publications
(62 reference statements)
0
3
0
Order By: Relevance
“…The phenomenon of capacity uctuation with unstable CE in the long-term cycling of U-Na//NVP is a common issue due to an unstable SEI, continuously reformed on the novel Na metal surface due to inhomogeneous plating and resulting massive dendrite growth, as has been reported previously for NVP cathodes in ether-based electrolytes. 76,77 From the selected discharge/charge proles as shown in Fig. 6b, the polarization between the charge and discharge plateaus of U-Na//NVP batteries sharply increases aer 60 cycles while the change in the polarization for P-Na//NVP is negligible.…”
Section: Resultsmentioning
confidence: 99%
“…The phenomenon of capacity uctuation with unstable CE in the long-term cycling of U-Na//NVP is a common issue due to an unstable SEI, continuously reformed on the novel Na metal surface due to inhomogeneous plating and resulting massive dendrite growth, as has been reported previously for NVP cathodes in ether-based electrolytes. 76,77 From the selected discharge/charge proles as shown in Fig. 6b, the polarization between the charge and discharge plateaus of U-Na//NVP batteries sharply increases aer 60 cycles while the change in the polarization for P-Na//NVP is negligible.…”
Section: Resultsmentioning
confidence: 99%
“…Besides the aforementioned strategies, the artificial SEI layer on Na metal anodes can also be attained via electrochemical methods and simple physical strategies (i.e., doctor blading and brushing), or even applied as accepted if commercially available. [ 148 ] For instance, an in situ formed IL membrane created by the electrochemical polymerization of reactive monomers as an artificial SEI on Na metal anodes was reported by Archer's group. [ 149 ] This method was first adopted to protect reactive Na metal anodes exhibiting prominent advantages of controlled film thickness and morphology.…”
Section: Stabilization Of the Sei On Na Metal Anodesmentioning
confidence: 99%
“…Notably, a direct strategy of a uniaxial compression loaded on a Na/NASICON assembly was proposed to tackle the interfacial crux. [166] The authors demonstrated that an interstitial layer was formed by pressing the Na metal on the NASICON surface, whereby Chemical pretreatments NaBr 1 m NaPF 6 in EC/PC 1 mA cm −2 ; 1 mA h cm −2 250 cycles 2017 [48] Bi 1 m NaCF 3 SO 3 in diglyme 0.5 mA cm −2 ; 1 mA h cm −2 1000 h 2019 [139] NaI 1 m NaCF 3 SO 3 in diglyme 0.25 mA cm −2 ; 0.75 mA h cm −2 500 h 2019 [140] PhS 2 Na 2 -rich layer 1 m NaPF 6 in EC/PC 1 mA cm −2 ; 1 mA h cm −2 800 h 2020 [141] Na 3 PS 4 1 m NaPF 6 in EC/PC 1 mA cm −2 ; 1 mA h cm −2 270 h 2019 [142] Thin film depositions PEALD-Al 2 O 3 1 m NaClO 4 in EC/DEC 0.25 mA cm −2 ; 1 mA h cm −2 400 h 2017 [144] ALD-Al 2 O 3 1 m NaSO 3 CF 3 in diglyme 3 mA cm −2 ; 1 mA h cm −2 500 h 2017 [61] MLD-alucone Na 3 PS 4 solid-state electrolyte 0.1 mA cm −2 ; 0.1 mA h cm −2 475 h 2020 [145] Free-standing protective films Graphene 1 m NaPF 6 in EC/DEC 2 mA cm −2 ; 3 mA h cm −2 300 h 2017 [146] Carbon paper 1 m NaCF 3 SO 3 in diglyme 5 mA cm −2 ; 1 mA h cm −2 1200 cycles 2018 [147] Others Nano-SiO 2 1 m NaPF 6 in diglyme 1 mA cm −2 ; 1 mA h cm −2 800 h 2019 [148] Ionic membrane 1 m NaClO 4 in EC/PC 0.1 mA cm −2 ; -250 h 2017 [149] Polished Na anode 1 m NaOTf in diglyme 5 mA cm −2 ; 2 mA h cm −2 550 h 2018 [150] Inorganic-organic hybrid protective layer 1 m NaPF 6 in diglyme 2 mA cm −2 ; 1 mA h cm −2 500 h 2019 [152] www.afm-journal.de www.advancedsciencenews.com…”
Section: Inorganic Solid Electrolytesmentioning
confidence: 99%